2020
DOI: 10.1051/e3sconf/202019707006
|View full text |Cite
|
Sign up to set email alerts
|

On the Design of a Diaphragm Valve for Aerostatic Bearings

Abstract: Because of their almost zero friction, cleanness and long life, aerostatic bearings are commonly used in many applications where high precision of positioning is required, e.g. machine tools, measuring machines, semiconductor manufacturing and power board testing. However, air bearings suffer from low relative stiffness and poor damping. Active and passive compensation are two effective methods to enhance the static and dynamic performance of these kinds of bearings. Despite their higher performance, active co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This paper presents a design procedure for a circular and centrally fed aerostatic pad controlled by a diaphragm As demonstrated by previous numerical and experimental works [29][30][31]33], this kind of compensation method makes it possible to significantly increase the static stiffness of air pads up to quasi-static infinite stiffness. Here, a design procedure is proposed to suitably select the geometry of this kind of passively compensated pad depending on the values of a desired air gap height at which the system has to work.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This paper presents a design procedure for a circular and centrally fed aerostatic pad controlled by a diaphragm As demonstrated by previous numerical and experimental works [29][30][31]33], this kind of compensation method makes it possible to significantly increase the static stiffness of air pads up to quasi-static infinite stiffness. Here, a design procedure is proposed to suitably select the geometry of this kind of passively compensated pad depending on the values of a desired air gap height at which the system has to work.…”
Section: Discussionmentioning
confidence: 96%
“…Chen and Lin [28] proposed an aerostatic pad with a disk spring compensator to increase the bearing damping. Ghodsiyeh et al [29,30] and Colombo et al [31,32] proposed a novel prototype of an aerostatic pad controlled by means of a diaphragm valve. It was found that this kind of passive compensation makes it possible to obtain quasi-static infinite stiffness and high damping in a low frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…It is convenient to calculate the constant static pressure P k0 at the outlet of the damping feeders and the corresponding pressure P p0 in the inter-throttling chambers using the normalized coefficients [18,21,28]…”
Section: Mathematical Modeling Of the Bearing Static State At Small Deviations Of The Moving Elements From The Central Equilibrium Positimentioning
confidence: 99%
“…Figure 5 shows the dependences of the compliance K on the adjustment factor χ for different values of the membrane elasticity coefficient K e for L = 1.5, λ 1 = L 1 /L = 0.2, λ 3 = L 3 /L = 0.15, P s = 5 and the recommended value of the weighting factor for the SECT adjustment ς = 0.15 [18,21]. For an absolutely rigid membrane (K e = 0), the K(K e ) dependence has a unimodal character, with a minimum compliance at χ ≈ 0.45.…”
Section: Mathematical Modeling Of the Bearing Static State At Small Deviations Of The Moving Elements From The Central Equilibrium Positimentioning
confidence: 99%
See 1 more Smart Citation